THE EXTERNAL DIMENSION OF MIGRATION POLICY IN THE MEDITERRANEAN REGION: PREMISES FOR NORMATIVE DEBATE (Journal of the Spanish Institute for Strategic Studies, 2018)
In recent years, policies on migratory flows have taken a new direction, based on an external dimension that entails the implementation of policy beyond state borders. This article aims to unravel the meaning of externalisation, which is not only seen as a new policy orientation, but also as a new discourse based on the idea that confrontation over migration between countries of origin and destination does not lead to the resolution of problems and that it is more beneficial for all parties to negotiate and cooperate.